Application of Wisdom's perturbative method for 5 : 2 and 7 : 3 resonances - Yokoyama, Tadashi [UNESP]; Balthazar, José Manoel [UNESP] (Academic Press Inc. Jnl-comp Subscriptions, 1992)
Wisdom's method is applied to 5 : 2 and 7 : 3 resonances. Comparisons with Yoshikawa's nontruncated model are performed: for moderate values of eccentricity, agreement is good, especially for the 5 : 2 resonance. A clear difference between the 5 : 2 and the 7 : 3 resonances is observed: the former (like the 3 : 1 resonance) can suffer significant variations of eccentricity, even starting from very small values close to 0, while the latter seems to undergo such variations but the minimum eccentricity cannot be less than a value near 0.1. In the 7 : 3 resonance, some chaotic motion trapped in a region of very small eccentricity is possible. This is in contrast with the 5 : 2 commensurability, since chaos in this case seems to be always related to significant variations of eccentricity. Recent calculations performed by Šidlichovskÿ using mapping techniques show agreement with the results presented here. © 1992.